Understanding enrolment in community health insurance in sub-Saharan Africa: a population-based case-control study in rural Burkina Faso - Manuela De Allegri; Bocar Kouyaté; Heiko Becher; Adjima Gbangou; Subhash Pokhrel; Mamadou Sanon; Rainer Sauerborn (Bulletin of the World Health Organization, 2006)
OBJECTIVE: To identify factors associated with decision to enrol in a community health insurance (CHI) scheme. METHODS: We conducted a population-based case-control study among 15 communities offered insurance in 2004 in rural Burkina Faso. For inclusion in the study, we selected all 154 enrolled (cases) and a random sample of 393 non-enrolled (controls) households. We used unconditional logistic regression (applying Huber-White correction to account for clustering at the community level) to explore the association between enrolment status and a set of household head, household and community characteristics. FINDINGS: Multivariate analysis revealed that enrolment in CHI was associated with Bwaba ethnicity, higher education, higher socioeconomic status, a negative perception of the adequacy of traditional care, a higher proportion of children living within the household, greater distance from the health facility, and a lower level of socioeconomic inequality within the community, but not with household health status or previous household health service utilization. CONCLUSION: Our study provides evidence that the decision to enrol in CHI is shaped by a combination of household head, household, and community factors. Policies aimed at enhancing enrolment ought to act at all three levels. On the basis of our findings, we discuss specific policy recommendations and highlight areas for further research.